The effect of process conditions in heat-assisted boronizing treatment on the tensile and bending strength characteristics of the AISI-304 austenitic stainless steel - Gunen, Ali; Kurt, Bulent; Somunkiran, Ilyas; Kanca, Erdogan; Orhan, Nuri (Maik Nauka/Interperiodica/Springer, 2015)
In this study, AISI 304 austenitic stainless steel surface was boronized with nanoboron and ekabor-III powders at 950 and 1000A degrees C for 2 and 4 hours period by solid-state box boronizing method. Then, behaviors of the boronized specimen in the microstructure, three-point bending, and tensile strength characteristics were investigated. As a result of the boriding process, the boride layer thickness in the range of 23-67 A mu m and microhardness value in the range of 1020-2200 HV have been obtained according to the increase in processing time and temperature and to the particle size of the boron source (0, 1). The coating layer on boronized specimens did not exhibit any sign of reaction caused by the tensile strength applied until the yield point was in both tests. Although the particle size of the boron agents was more effective on the boronized specimen's bending and tensile strength behaviors, it was observed that processing temperature and its duration are effective as well.
Keywords: nanoboron; ekabor; boride layer; tensile strength; bending strength